The Implementation of Yusuf Al-Qaradawi’s Method of Understanding Hadith Regarding the Fatwa on the Meaning of Fi Sabilillah in the Context of Zakat - Yusronil Haq, Ahmad; Kholishudin (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2025)
This study aims to implement Yusuf al-Qaradawi’s method of understanding hadith in Kaifa Nata‘amal ma‘a al-Sunnah al-Nabawiyyah regarding the hadiths used as the basis for his fatwa on the the